Using Sonic Log to Predict Abnormal Pressure Zones in Selected Oil Wells (Western of Iraq) - A. Saleh, Talib (Iraqi Journal of Chemical and Petroleum Engineering, 2014)
Two oil wells were tested to find the abnormal pressure zones using sonic log technique. We found that well Abu-Jir-3 and Abu-Jir-5 had an abnormal pressure zones from depth 4340 to 4520 feet and 4200 to 4600 feet, respectively. The maximum difference between obtained results and the field measured results did not exceed 2.4%.In this paper, the formation pressures were expressed in terms of pressure gradient which sometimes reached up to twice the normal pressure gradient.Drilling and developing such formations were dangerous and expensive.The plotted figures showed a clear derivation from the normal trend which confirmed the existence of abnormal pressure zones.